Pengaruh Corporate Governance, Operating Capacity, Leverage, Likuiditas, dan Ukuran Perusahaan terhadap Financial Distress Perusahaan Sektor Aneka Industri - Hikmawati, Vara Buananta (Jurnal Ilmu Manajemen, 2022)
Financial distress is a situation that occurs when a company have unhealthy financial conditions. If this condition occurs sustainably, it will impact the company’s bankruptcy. This research aims to determine the effect of corporate governance, operating capacity, leverage, liquidity, and firm size. The independent variables in corporate governance include institutional ownership, managerial ownership, and an independent board of commissioners. This research’s population are companies in the miscellaneous industry sectors listed on the Indonesia Stock Exchange from 2017 to 2020. The sample retrieval technique uses purposive sampling and obtained 15 companies as samples in this research. The data were analysed using logistic regression and calculated with IBM SPSS 25. The result showed that an independent board of commissioners significantly and negatively impacted financial distress. Leverage (debt to assets ratio) and firm size significantly and positively affected financial distress. While institutional ownership, managerial ownership, operating capacity (total assets turnover), and liquidity (current ratio) don’t significantly impact financial distress. Therefore, companies in the miscellaneous industry sectors can give more attention to the role of institutional and managerial ownership to avoid financial distress.